Pengetahuan Petani Pisang Terhadap Prosedur Untuk Mendapatkan Pembiayaan. (Kasus di Kelompok Tani Sagara, Desa Kanoman, Kecamatan Cibeber Kabupaten Cianjur) - Siti Haryanti; Eliana Wulandari (Universitas Tadulako, 2018)
ABSTRACTThe purpose of this research was to analyze farmer’s knowledge on the procedure to obtain credit from bank and factors related to the farmer’s knowledge. This research used a quantitative method. The data were collected by interviewing and distributing questionnaires to forty banana farmers. Gap analysis and Ordinary Least Square were performed in this study. Procedures to access to finance from banks are farmers must submit a letter of credit application by filling the loan application form provided by the banks, the evaluation of the collateral value or guarantee by the banks, the decision to accept the credit by the banks, and the existence of monthly evaluation activities by the bank to the debtors after the credit disbursement. The results showed that the average score of farmers’ knowledge on the procedure to obtain finance from bank was 0.44. This means that the farmers’ knowledge on the procedure to obtain finance from bank was relatively low. This is due to significant factors related to the procedure, i.e. experience in obtaining finance and information sources.Keywords: Banks, Farmers’ knowledge, procedures to obtained finance,